Peran Mahasiswa dalam Meningkatkan Kualitas Pendidikan Agama Islam di TPA Sulamunajah Kelurahan Tanjung Pinang - Satria Satria; Aufiana Firda; Choirula Oktavia Nissa; Ayu Andini Harahap; Siti Fatimah Azzahra; Annisa Annisa; Abdullah Abdullah (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
Tanjung Pinang is one of the sub-districts in Pahandut District, Palangka Raya City, Central Kalimantan Province, Indonesia. The role of students in community service or what is usually called real work lectures (KKN) increases the value of the quality of Islamic religious education. With the knowledge they have and the presence of KKN students, they have a significant impact in the religious field. The strategy used in implementing this activity is to plan and optimize joint activities to follow up on ideas that arise. From this plan, it will be identified who will coordinate and who should be responsible for each stage of the activity. The role of students in improving the quality of Islamic religious education at TPA Sulamanajah, Tanjung Pinang District. This research aims to analyze the strategy and impact of the student KKN program in improving the quality of Islamic religious education at TPA Sulamanajah. Increasing activities with Islamic religious values ​​for children provides benefits to the surrounding community. Not only as a means to get closer to Allah SWT, but also as a main factor in increasing the potential of Human Resources (HR) who are competent, aspirational and solid and responsible for the Muslim community. This type of research uses qualitative methods, with the aim of describing the phenomena that occur (qualitative descriptive). This type of research is field research, namely research where data collection is carried out in the field. In this case it was carried out in Tanjung Pinang Village. The location of this research was carried out at the location that was the source of the research, namely in Tanjung Pinang Village.